Evaluating the circular economy for sanitation: findings from a multi-case approach - Mallory, Adrian; Akrofi, Daniel; Dizon, Jenica; Mohanty, Sourav; Parker, Alison; Rey Vicario, Dolores; Prasad, Sharada S.; Welvita, Indunee; Brewer, Timothy R.; Mekala, Sneha; Bundhoo, Dilshaad; Lynch, Kenny; et al. (Elsevier, 2020)
Addressing the lack of sanitation globally is a major global challenge with 700 million people still practicing open defecation. Circular Economy (CE) in the context of sanitation focuses on the whole sanitation chain which includes the provision of toilets, the collection of waste, treatment and transformation into sanitation-derived products including fertiliser, fuel and clean water. After a qualitative study from five case studies across India, covering different treatment technologies, waste-derived products, markets and contexts; this research identifies the main barriers and enablers for circular sanitation business models to succeed. A framework assessing the technical and social system changes required to enable circular sanitation models was derived from the case studies. Some of these changes can be achieved with increased enforcement, policies and subsidies for fertilisers, and integration of sanitation with other waste streams to increase its viability. Major changes such as the cultural norms around re-use, demographic shifts and soil depletion would be outside the scope of a single project, policy or planning initiative. The move to CE sanitation may still be desirable from a policy perspective but we argue that shifting to CE models should not be seen as a panacea that can solve the global sanitation crisis. Delivering the public good of safe sanitation services for all, whether circular or not, will continue to be a difficult task